In vitro antifungal activity of lactic acid bacteria low molecular peptides against spoilage fungi of bakery products - Muhialdin, BJ; Hassan, Z; Saari, N (Springer, 2024)
Bio-preservation, a promising preservation method that involves the use of "friendly" microorganisms such as lactic acid bacteria, has recently become a topic of considerable interest. In the present study, 16 lactic acid bacteria isolates were evaluated for antifungal activity against six fungi commonly associated with bread spoilage. The antifungal compounds were heat stable at 121 A degrees C, and only four isolates, DU15, IT10, TE10, and IS10, showed partial loss of activity when supernatants were treated with proteolytic enzymes. The four isolates showed high inhibition activity at pH 3 and were identified using 16S rDNA sequencing as belonging to Leuconostoc mesenteroides DU15, Lactobacillus plantarum TE10, Lactobacillus plantarum IT10, and Lactobacillus plantarum IS10. The minimum germination inhibitions were 30 mg, 50 mg, 40 mg, and 50 mg for TE10, IT10, DU15, and IS10 respectively. The optimum conditions for the strains to produce antifungal compounds were 37 A degrees C for 48 h for IT10, IS10, and TE10, and 30 A degrees C for 24 h for DU15. Antifungal activity was increased threefold when supernatants were filtered using 10 KDa membranes. These findings demonstrate the potential of using lactic acid bacteria antifungal peptides as natural preservatives in bakery products to control the growth of spoilage fungi.